PENGARUH MEDIA ANIMASI DALAM POWERPOINT TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 1 KEPIL KECAMATAN KEPIL, KABUPATEN WONOSOBO - Wimbo Dwi Antoro; Dwi Winarsih; Widiasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to analyze the effect of using animated PowerPoint media on learning motivation and science learning outcomes of fifth-grade students at SD Negeri 1 Kepil, Wonosobo Regency. The background of this research is the low motivation and science achievement of students, partly caused by the use of conventional learning media that lack interactivity and visualization. A quasi-experimental method with a two-group pretest–posttest design was employed. The experimental class used PowerPoint integrated with animation, while the control class used conventional PowerPoint without animation. Data on learning motivation were obtained through a Likert-scale questionnaire, and learning outcomes were measured through multiple-choice tests. Data analysis used descriptive statistics and an independent sample t-test after meeting the assumptions of normality and homogeneity. The findings showed that the experimental group experienced a greater improvement than the control group, with an N-Gain average of 0.68 for learning outcomes and 0.45 for motivation. The t-test results indicated a significant difference (p < 0.05) between the two groups. These results confirm that animated PowerPoint media can increase both students’ motivation and science learning outcomes. The study concludes that integrating animation into PowerPoint presentations makes learning more engaging, interactive, and effective for elementary school students.